(untitled) (Journal of Social Sciences Review, 2023)
University teachers’ methods are essential for students learning. At this point, teachers can teach students how to think critically, which helps them solve problems that are important for a country’s social and economic progress. Teachers help students get ready for their future jobs. They also show what to do. So, students must know how their teachers’ methods help them. Teachers use complicated teaching tactics and intentions when teaching. The Approaches to Teaching Inventory is a reliable and valid survey tool used in this quantitative study to look at university professors in Punjab, Pakistan. One hundred twenty university teachers were chosen by cluster stratified random sampling. Based on this study, teachers use techniques like Conceptual Change-Student-Focused and Information Transmission-Teacher-Focused. Both public and private universities teach the same way. This study suggests that university teachers should get more training in teaching methods.